#1**+5 **

X^2-12X+27=0

The right side can be factored out. Think, what times what equals 27, and have those two numbers add up to -12, well it turns out that -9 and -3 work, because -3 x -9 = 27, and -3 + -8 = 12.

(x-9)(x-3)=0

Now use the "zero product property" which says that if you have two numbers multiplied together equal zero, then one of these numbers *has to be* zero. This means we can set each factor to 0, and solve.

(x-9)(x-3)=0 ---Set each factor to zero

(x-9) = 0 | (x-3)=0

+9 +9 +3 +3

----------------------------

x = 9 | x = 3

The two solutions are **x = 9** and **x = 3**.

NinjaDevo Oct 4, 2014

#1**+5 **

Best Answer

X^2-12X+27=0

The right side can be factored out. Think, what times what equals 27, and have those two numbers add up to -12, well it turns out that -9 and -3 work, because -3 x -9 = 27, and -3 + -8 = 12.

(x-9)(x-3)=0

Now use the "zero product property" which says that if you have two numbers multiplied together equal zero, then one of these numbers *has to be* zero. This means we can set each factor to 0, and solve.

(x-9)(x-3)=0 ---Set each factor to zero

(x-9) = 0 | (x-3)=0

+9 +9 +3 +3

----------------------------

x = 9 | x = 3

The two solutions are **x = 9** and **x = 3**.

NinjaDevo Oct 4, 2014